Analisis Framing Pemberitaan Pemilu Presiden 2024 di Media Online Detik.com Periode Bulan Februari - Harahap, Tondini Alief; Harahap, Aprilinda (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study raises a study of the analysis of the framing of the 2024 election news, specifically the news of the presidential and vice presidential candidates which focuses on the framing of the news published by the detik.com media, furthermore, the writing of this article uses a qualitative research method that uses a research approach and analysis of news about the presidential candidates in February, in line with that the framing analysis included in the results of this study uses the framing analysis proposed by Robert M. Etnman which emphasizes four main aspects of analysis such as, problem definition, diagnosis of causes, moral assessment and recommendations for resolution. The final results of this study conclude that detik.com's news in February regarding the 2024 presidential election highlights statements from each candidate and also the campaign teams and several other aspects, and also provides positive moral assessments and sentiments in several aspects, and limits several issues that need to be limited, but not all news meets the four aspects of Robert M. Etnman's analysis method, such as not explaining the background of the problem and also recommendations for resolution. This study focuses on how the media has a central role in forming public assumptions in the 2024 presidential election.